The death of Dick Long [videorecording (DVD)] - Scheinert, Daniel; Scheinert, Daniel; Abbott, Michael, Jr., 1978-; Newcomb, Virginia; Hyland, Andre, 1979- (Lionsgate, 2019)
Follows Zeke and Earl in small-town Alabama as they try to cover up how their friend and bandmate Dick died.